Dissatisfaction Risk Factors of Patients after Laminectomy for Thoracic Ossification of Ligamentum Flavum: A Retrospective Cohort Study of Different Follow-Up Periods. (20th December 2021) - Wang, Zhiwei; Yang, Sidong; Gao, Xianda; Wang, Zheng; Ding, Wenyuan; Yang, Dalong
Abstract : Objectives . To explore the influencing factors of satisfaction with postoperative treatment in patients diagnosed with thoracic ossification of the ligamentum flavum during different follow-up periods. Methods . This was a retrospective study of 57 patients who were diagnosed with thoracic ossification of ligamentum flavum (TOLF) and treated with laminectomy in the Spine Surgery Department of the Third Hospital of Hebei Medical University from January 2010 to January 2017. The Patient Satisfaction Index (PSI) was collected at discharge and at 6-month, 1-year, and the last follow-up. According to the evaluation results, the patients could be divided into a satisfied group and a dissatisfied group. The patient's Japanese Orthopaedic Association (JOA) score improvement rate was evaluated at the last follow-up. Possible influencing factors of the two groups of patients were compared and the related influencing factors of satisfaction with postoperative treatment in patients during different follow-up periods were summarized. Results . At the time of discharge, the dissatisfied and satisfied groups had significant differences in variables of diabetes mellitus, duration of preoperative symptoms, urination disorder, intramedullary signal change on MRI, dural ossification, residual rate of cross-sectional spinal canal area on CT, shape on the sagittal MRI, hospital stay, hospitalization expenses, postoperative pain in LE VAS, delayed wound healing, postoperative depression, and intercostal pain (P < 0.05 ). There were also significant differences in urination disorder, postoperative pain according to the LE VAS, JOA score, and postoperative depression during the 6-month follow-up (P < 0.05 ). There were no significant differences in other variables between the two groups (P > 0.05 ). One year after the operation, there were significant differences between the dissatisfied group and the satisfied group in urination disorder, JOA score, and symptom recurrence (P < 0.05 ). There were also significant differences in the JOA score and symptom recurrence at the final follow-up (P < 0.05 ). For further analysis, the duration of preoperative symptoms in the satisfied group was less than 24 months and the duration of preoperative symptoms in the dissatisfied group was more than 24 months. The JOA scores of patients in the satisfied group and the dissatisfied group increased gradually with the improvement of neurological function in different follow-up periods, but, at the last follow-up, the JOA scores of patients in the satisfied group were significantly higher than those in the dissatisfied group. Conclusions . In conclusion, for thoracic ossification of ligamentum flavum patients who received laminectomy, dissatisfaction with the early and medium-term postoperative results may be related to diabetes, the duration of preoperative symptoms, hospitalization expenses, delayed wound healing, intercostal pain, and urination disorder, and dissatisfaction with the long-term postoperative results might be related to the low JOA score improvement rate and symptom recurrence.